OPTIMIZING SURFACE STERILIZATION OF Lansium domesticum LEAF LAMINA EXPLANTS USING SODIUM HYPOCHLORITE - Irmawati, Irmawati; Susilawati, Susilawati; Helen, Helen; Inaya, Rihani; Herlin, Weri (LPPM Universitas Jambi, 2026)
Lansium domesticum Corr. is a fruit crop with high consumer demand; however, its conventional propagation is relatively slow. In vitro culture offers a potential alternative to accelerate plant propagation. This study aimed to evaluate sodium hypochlorite (NaOCl)-based sterilization protocols and identify the most effective treatment for in vitro establishment of leaf lamina explants. The experiment was conducted at the Tissue Culture Laboratory, Faculty of Agriculture, Universitas Sriwijaya, from July to September 2024 using five sterilization treatments with different NaOCl concentrations and exposure times. Data were analyzed descriptively to determine the percentages of bacterial contamination, fungal contamination, surviving explants, and browning incidence. The results showed that the treatment consisting of liquid detergent (3 min), 0.2% streptomycin sulfate (10 min), 0.2% benomyl (10 min), 1% NaOCl (15 min), and 70% ethanol (5 min) was the most effective protocol. This treatment resulted in 63% explant survival, 0% browning, 33% bacterial contamination, and 3% fungal contamination. This study provides a practical sterilization protocol that balances antimicrobial effectiveness and tissue viability, representing a novel contribution for in vitro propagation of Lansium domesticum. The findings have important implications for improving large-scale propagation efficiency of this economically important tropical fruit species. These results indicate that moderate NaOCl exposure is essential to achieve an optimal balance between contamination control and explant viability in in vitro culture systems.